2013
DOI: 10.1111/ppa.12036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flooding on the survival of Leptosphaeria spp. in canola stubble

Abstract: This study used a versatile temperature-control device to assess the effect of temperature (12-40°C) and duration (2-12 weeks) of flooding on the survival of Leptosphaeria spp. in canola (Brassica napus) stubble. Canola basal stems with blackleg symptoms were submerged in water in small glass jars containing 20 cm 3 soil on a thermogradient plate capable of simultaneously maintaining up to 96 independent temperature regimes. Flooded stems were sampled at 2-week intervals, surface-sterilized, and incubated on V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Destruction of blackleg-infested stubbles by tillage has been recommended. A paddy rice crop following winter canola in some canola growing regions of China has been proven to be able to minimize the impact of inoculum in stubble (Peluola et al 2013). In Australia, new canola crops are recommended to be grown at least 500 meters from previous year's canola stubble (Marcroft et al 2003).…”
Section: Disease Managementmentioning
confidence: 99%
“…Destruction of blackleg-infested stubbles by tillage has been recommended. A paddy rice crop following winter canola in some canola growing regions of China has been proven to be able to minimize the impact of inoculum in stubble (Peluola et al 2013). In Australia, new canola crops are recommended to be grown at least 500 meters from previous year's canola stubble (Marcroft et al 2003).…”
Section: Disease Managementmentioning
confidence: 99%
“…The diversity of soil microbial communities increases with increasing soil water content (SWC) in arid and semi-arid ecosystems, but SWC has no major effect on the diversity of soil microbial communities in wetland ecosystems (Cregger et al, 2012;Manzoni et al, 2012). Increasing evidences have fulfilled the gap between the short-and long-term flooding effects on soil microbial communities (Peluola et al, 2013). In environmental ecology, it is observed that flooding has important effects on the underground microbial environment (Shen et al, 2021), but the impact of varying degrees of flooding in agriculture ecology on the crop performance and microbial characteristics is still little known.…”
Section: Introductionmentioning
confidence: 99%
“…In China winter oilseed rape is often followed by several weeks of flooding with a paddy rice crop [ 14 ]. It has been reported that flooding can rapidly reduce the survival of the Blackleg pathogen in canola stubble [ 15 ]. L. maculans is considered a global invasive species, it has recently spread across Canada (1975–1998), from the USA into Mexico (2001) and eastwards across Europe into Poland (1994–2007), where only the less damaging L. biglobosa was previously present [ 1 ].…”
Section: Introductionmentioning
confidence: 99%